Evaluating the Effectiveness of Measles Surveillance Systems in Africa: A Systematic Review of Epidemiological Trends, and Laboratory Performance: Evaluating the Effectiveness of Measles Surveillance Systems in Africa - Kayode Akanbi; Olanrewaju Olaiya; Islamiyyat Adekemi Olatinwo; Imaobong Udo Isang; Sunday Thomas Sola (Journal of Epidemiology and Public Health, 2025)
Background: As efforts to eliminate measles advance, it becomes essential to enhance the sensitivity of surveillance systems. This involves identifying and thoroughly investigating all cases presented with fever and rash. This systematic review evaluates the effectiveness of measles surveillance systems in Africa, focusing on epidemiological trends, vaccination coverage, and laboratory performance. Methodology: A comprehensive search strategy was employed across five databases, PubMed, MEDLINE, Embase, Scopus, and Google Scholar—to identify peer-reviewed studies published between 2014 and 2024. From an initial pool of 124 articles, eight met the inclusion criteria and were critically appraised using both quantitative and qualitative tools. Result: The findings highlight several systemic challenges, including the sub-optimal performance of measles surveillance systems, gaps in immunization coverage, and significant regional disparities in disease burden. Common deficiencies include inadequate case reporting, limited laboratory capacity, and insufficient training of frontline health workers. Moreover, low vaccine uptake, especially for the second dose (MCV2)—was attributed to supply chain issues, vaccine hesitancy, and geographic barriers. Conclusion: The review underscores the urgent need for improved laboratory infrastructure, expanded training, community engagement, and equitable access to immunization services. Strengthening these areas is critical to enhancing measles surveillance and achieving elimination goals across the continent. Keyword: Measles, surveillance systems. Laboratory performance, immunization.